SOME ASPECTS OF USING ELECTRONIC LITERATURE IN TEACHING PHYSICS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the need to improve the methodology for using electronic textbooks in teaching physics, the organization and implementation of virtual laboratory classes in the process of teaching physics in military educational institutions, and demonstrates the procedure and advantages of conducting virtual laboratory classes.